Spatial and temporal changes in the coupling of ecological environment and tourism development: the case of Kyushu, Japan. (1st January 2023) - Liu, Yiming; Suk, Sunhee; Cai, Yanning
Abstract: The relationship between the ecological environment and tourism development is extremely complex. Summarizing evolutionary trends, temporal patterns and spatial differences in time and space can contribute to the coordinated development of an ecological environment and tourism. Based on the Carrying capacity–Supporting capability–Attraction capability–Evolutional capability–Development capability model and the Pressure–State–Response model, this paper proposes a conceptual index system using the entropy weight method and the coupled coordination degree model. The coupling coordination relationship between the ecological environment and tourism development in seven prefectures in the Kyushu region of Japan from 2010 to 2019 was analyzed. Then, using the membership degree model, the coordinated development of each prefecture was further analyzed. The results mainly show that in the Kyushu region, the degree of coupling coordination between the ecological environment and the tourism development system changed from moderate coordination to marginal coordination during the study period, then steadily improved, with large differences between regions. Based on the analysis results, this paper puts forward specific suggestions for the prefectures with lagging tourism development and lagging ecological environment development, respectively, to provide a reference path for the sustainable development of the ecological environment and tourism in the Kyushu region. For prefectures in the ecological environment development lag-type stage, the following requirements were identified: (a) the need for the government to strengthen tourism infrastructures; (b) the need for the government to focus on developing regional ecotourism, focusing on the fragility of island ecosystems and the sustainability of resources in the Kyushu region; (c) the need for the government to scientifically formulate tourism-related policies and plan tourism-related investments. For prefectures in the tourism development lag-type stage, the following were identified: (a) the need for the government to develop a variety of tourism products and create regional tourism brands based on local conditions; (b) prefectures should determine the main tourism functions and themes it offers based on the specifics of their resource advantages.